Green Synthesis of Silver Nanoparticles Using Euphorbia wallichii Leaf Extract: Its Antibacterial Action against Citrus Canker Causal Agent and Antioxidant Potential - Muhammad Arif; Rahim Ullah; Maaz Ahmad; Ahmad Ali; Zahid Ullah; Mohammad Ali; Fakhria A. Al-Joufi; Muhammad Zahoor; Hassan Sher (Molecules, 2022)
Biologically synthesized silver nanoparticles are emerging as attractive alternatives to chemical pesticides due to the ease of their synthesis, safety and antimicrobial activities in lower possible concentrations. In the present study, we have synthesized silver nanoparticles (AgNPs) using the aqueous extract of the medicinal plant Euphorbia wallichii and tested them against the plant pathogenic bacterium Xanthomonas axonopodis, the causative agent of citrus canker, via an in vitro experiment. The synthesized silver nanoparticles were characterized by techniques such as UV-Vis spectroscopy, Fourier transform infrared spectroscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction analysis and transmission electron microscopy. Moreover, the plant species were investigated for phenolics, flavonoids and antioxidant activity. The antioxidant potential of the extract was determined against a DPPH radical. The extract was also evaluated for phenolic compounds using the HPLC technique. The results confirmed the synthesis of centered cubic, spherical-shaped and crystalline nanoparticles by employing standard characterization techniques. A qualitative and quantitative phytochemical analysis revealed the presence of phenolics (41.52 mg GAE/g), flavonoids (14.2 mg QE/g) and other metabolites of medicinal importance. Different concentrations (1000 µg/mL to 15.62 µg/mL—2 fold dilutions) of AgNPs and plant extract (PE) alone, and both in combination (AgNPs-PE), exhibited a differential inhibition of X. axanopodis in a high throughput antibacterial assay. Overall, AgNPs-PE was superior in terms of displaying significant antibacterial activity, followed by AgNPs alone. An appreciable antioxidant potential was recorded as well. The observed antibacterial and antioxidant potential may be attributed to eight phenolic compounds identified in the extract. The Euphorbia wallichii leaf-extract-induced synthesized AgNPs exhibited strong antibacterial activity against X. axanopodis, which could be exploited as effective alternative preparations against citrus canker in planta in a controlled environment. In addition, as a good source of phenolic compounds, the plant could be further exploited for potent antioxidants.